2017
DOI: 10.18632/oncotarget.20752
|View full text |Cite
|
Sign up to set email alerts
|

Trimedazidine alleviates pulmonary artery banding-induced acute right heart dysfunction and activates PRAS40 in rats

Abstract: The molecular mechanism underlying acute right heart failure (RHF) is poorly understood. We used pulmonary artery banding (PAB) to induce acute RHF characterized by a rapid rise of right ventricular pressure, and then a decrease in right ventricular pressure along with a decrease in blood pressure right after banding. We found higher brain natriuretic peptide (BNP) and beta-myosin heavy chain (βMHC) levels and lower alpha-myosin heavy chain (αMHC) levels in RHF rats than sham-operated rats. Hemodynamic indexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Therefore, a rat model of PAB was adopted, because no pathological changes have been observed in the pulmonary parenchyma of this rat model and its phenotypes of acute RHF are predominantly, if not completely, caused by simple increase of afterload. 4 In the current study, also in the previous study, 10 we clipped the main pulmonary artery to induce a rapid increase in RV afterload and acute RHF. Afterwards, the high-throughput RNA-seq combined with bioinformatics analyses were employed to analyse gene expression profiling of the experimental groups.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Therefore, a rat model of PAB was adopted, because no pathological changes have been observed in the pulmonary parenchyma of this rat model and its phenotypes of acute RHF are predominantly, if not completely, caused by simple increase of afterload. 4 In the current study, also in the previous study, 10 we clipped the main pulmonary artery to induce a rapid increase in RV afterload and acute RHF. Afterwards, the high-throughput RNA-seq combined with bioinformatics analyses were employed to analyse gene expression profiling of the experimental groups.…”
Section: Discussionmentioning
confidence: 52%
“…The RV catheterization and PAB were performed as previously described. 10 Briefly, the rats were intubated with a 16-gauge Teflon tube and attached to a mechanical ventilator (Micro-Ventilator, UNO, Zevenaar, Netherlands) with the breathing frequency of 80 breaths / min, the pressures at 9/0 cmH 2 O, and the inspiratory/expiratory ratio of 1:1. The heads and limbs of the animals were fixed on an operating table.…”
Section: Methodsmentioning
confidence: 99%
“…Models of transient pulmonary artery occlusion increase RV afterload by mechanical constriction of the pulmonary artery from the exterior or by inflation of intravascular balloons (48). External occlusion can be applied by ligature (43,44), snares (42), simple banding (40), or more advanced adjustable bands using air (41,45,46). The occlusion, and hence the PVR and RV strain, can be adjusted very precisely and, as opposed to PE models, the resistance can be reduced or even removed as the occlusion can be re-loosened.…”
Section: Models Of Transient Pulmonary Artery Occlusionmentioning
confidence: 99%
“…Accumulating studies have suggested that the PGC-1α level is significantly decreased in various models of heart failure 81, 82. Additionally, activation of PGC-1β gene has been shown to also be reduced in response to chronic pressure overload, but is also dependent on, and responsive to, the chemical form of exogenous and dietary long chain fatty acids 6.…”
Section: The Role Of Pgc-1 In Heart Failurementioning
confidence: 99%